2020
DOI: 10.3390/ijms21239193
|View full text |Cite
|
Sign up to set email alerts
|

Novel Neuroprotective Agents to Treat Neonatal Hypoxic-Ischemic Encephalopathy: Inter-Alpha Inhibitor Proteins

Abstract: Perinatal hypoxia-ischemia (HI) is a major cause of brain injury and mortality in neonates. Hypoxic-ischemic encephalopathy (HIE) predisposes infants to long-term cognitive deficits that influence their quality of life and place a large burden on society. The only approved treatment to protect the brain after HI is therapeutic hypothermia, which has limited effectiveness, a narrow therapeutic time window, and is not considered safe for treatment of premature infants. Alternative or adjunctive therapies are nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 103 publications
0
12
0
Order By: Relevance
“…Birth asphyxia is the most common risk factor for early neonatal death, followed by premature delivery, low birth weight, and infection [ 1 ]. The exploration of the pathological mechanism of neonatal asphyxia found that hypoxia and ischemia can make the nutrition and energy supply of the neonatal brain abnormal, which in turn leads to neuronal cell death, cell dysfunction, and neurodevelopmental defects [ 2 ]. Neonatal hypoxic-ischemic encephalopathy (NHIE) is one of the serious complications of perinatal asphyxia, and its etiology is related to impair ND [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Birth asphyxia is the most common risk factor for early neonatal death, followed by premature delivery, low birth weight, and infection [ 1 ]. The exploration of the pathological mechanism of neonatal asphyxia found that hypoxia and ischemia can make the nutrition and energy supply of the neonatal brain abnormal, which in turn leads to neuronal cell death, cell dysfunction, and neurodevelopmental defects [ 2 ]. Neonatal hypoxic-ischemic encephalopathy (NHIE) is one of the serious complications of perinatal asphyxia, and its etiology is related to impair ND [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, there is a decrease in the activity of enzymes -inactivators of free radicals and many other components of AODS. Studies show that the activity of AODS enzymes such as GPx, catalase CT, and SOD tends to increase with an increase in the gestational age of a newborn [1,2,6,8].…”
Section:  Results and Discussionmentioning
confidence: 99%
“…Insuffi cient content of HS groups in blood plasma in severe neonatal conditions indicates a decrease in the activity of the glutathione system, which is associated with both insuffi cient production of reduced glutathione and an increase in its breakdown for FR inactivation. According to the references, the main component of HS groups in blood plasma is HS groups of proteins [2,6,23].…”
Section: оригинальные исследованияmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxic-ischemic encephalopathy predisposes infants to long-term cognitive decline impacting on life quality and healthcare resources ( Chen et al, 2019 ). ITI regulates neonatal inflammation, decreases damage to brain tissues ( Chen et al, 2019 ) and neuronal cell death, attenuates glial responses and leucocyte invasion with long-term beneficial effects in neonatal models of brain injury ( Koehn et al, 2020 ).…”
Section: The Small Neural Proteoglycansmentioning
confidence: 99%